Application of Multiolication Pocket Board Media to Improve Student Understanding in Mathematics Learning in Elementray Schools - Ayu Rachmadi, Tiara; Zubaidi, Zubaidi; Miftachudin, Miftachudin (Program Studi PGMI, 2025)
This study aims to implementation of learning media can help develop student understanding in learning grade 3 mathematics. Observations in class 3 UPTD SDN Bojong 1 Tangerang in September 2024 also showed the problem of students' lack of understanding in learning mathematics on multiplication material. Nurhamidah said that students' lack of understanding of learning can affect their learning outcomes. Therefore, learning media able to be the solution to develop student understanding in learning mathematics (Sellafeni et al., 2023). For that reason, it is necessary to carry out study to identify factors that influence student understanding in learning mathematics. This research tends to identify factors that influence students' understanding of mathematics learning and develop effective learning strategies to improve students' understanding of mathematics learning, especially on multiplication material. The use of multiplication bag board media in grade 3 school basic multiplication material has a positive influence on student understanding in learning mathematics. As one of the factors, Learning media plays an fundamental role in the teaching and learning process.Teachers in learning usually employ learning media as an intermediary in delivering material to make the students understand it. This research uses the development method (Research and Development), which was developed with the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. By using the R&D method, researchers can develop innovative and effective products, processes, or systems to solve problems or meet needs. This study was held at SDN Bojong 1 Tangerang, while the subjects involved in this research were grade 3 students. The data obtained from the research subjects were collected through observation methods and student grades.